A dança na escola e a constituição de identidades juvenis - PAZ, Ataíze Gonçalves (2019)
The present work deals with an ethnographic research, carried out at Escola Cristo Trabalhador, focusing on the Educar Group for Research and its members. The objective was to investigate the constitution of the identities of students participating in the Group. As instruments of information production I used the participant observation, the capture of images, the conversation, the questionnaire, that served for the composition of the field diary. The subjects of the research were students participating in the Educate for Research Project, some employees of the institution and a group of teachers. The research problem presents the following questions: How does dance contribute to the identities of students of the Cristo Trabalhador School? To help the reflection I will count with Bourdieu (1983), Canclini (1989), Dayrell (2007), Ribeiro (2013) and Silva (2000). As a result I emphasize that dance is a cultural manifestation that assists in the constitution of students' identities, since participating in the dance group provides students with an understanding of themselves and what is around them; also emphasized how the Project to educate by the research encourages the ethical formation and citizens of the students due to the multicultural present in this space.